2015
DOI: 10.1007/s12328-015-0597-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte depletion syndrome (McKittrick–Wheelock syndrome) successfully treated by endoscopic submucosal dissection

Abstract: A 66-year-old woman presented to us with malaise, anorexia and rectal mucous discharge, and her laboratory data showed severe hyponatremia, hypokalemia, hypochloremia and renal failure. Computed tomography revealed massive occupation of the rectum by a large tumor. Colonoscopy revealed a mucus-rich villous tumor in the rectum. As there were no other factors that could cause an electrolyte disorder, she was diagnosed with McKittrick-Wheelock syndrome (MWS). The current standard treatment for MWS is partial surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…It is defined by the triad of electrolyte disorders, kidney injury secondary to fluid depletion and chronic secretory diarrhea caused by a large rectal neoplasm [1][2][3][4][5][6][7][8][9][10]. Renal adaption and increased oral intake may initially compensate for the fluid and electrolyte losses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is defined by the triad of electrolyte disorders, kidney injury secondary to fluid depletion and chronic secretory diarrhea caused by a large rectal neoplasm [1][2][3][4][5][6][7][8][9][10]. Renal adaption and increased oral intake may initially compensate for the fluid and electrolyte losses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition adenoma's can degenerate into an adenocarcinoma. The majority of McKittrick-Wheelock syndromes are due to large (>3-4cm), mucus-rich villous adenoma in the distal part of the colon [1][2][3][4]7]. In a recent case review performed by Sarthak M et al [1], out of 35 found cases 22 had a villous adenoma, 8 had an underlying adenocarcinoma, one had a hyperplastic polyp and one had a neuro-endocrine tumor with liver metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported complications in the literature included associated endocarditis (19), pseudoobstruction (32), rhabdomyolysis (20), clostridium difficle induced diarrhea (33), intussception and rectal prolapse (12). Postoperative complications such as postoperative stricture (29) have been reported which require multiple sessions of rectal dilatations.…”
Section: Discussionmentioning
confidence: 99%